The overview of the concept of agriculture 4.0 and its possible ways of innovation - Dajka, Máté Ferenc; Oláh, Izabella (Studia Mundi – Economica, 2023)
Agriculture 4.0 is a term borrowed from the history of industrial development, which refers to the fact that in the earlier stages of the history, every time a few significant technological innovations were at the center of the process, which determined the long-term development of the sector. In the case of today's agriculture, this technological development is represented by digitization and the appearance of data-based decision-making management. Some stages of agricultural development are based on each other, without the spread of the former, we cannot talk about the appearance of the subsequent one either: without computer systems and precision farming, the appearance of data-based farming is also impossible. The data used in everyday farming can be divided into different groups but storing them in an integrated system and processing them with suitable methods makes farming easier and gives the farmer an advantage in market. Comparing data-based management with the spread of previous innovations, a conclusion can be drawn: we are in the early stages of a new technological development cycle. At the stage 4.0, the main function of these systems is supporting decision making, but it is expected that they will play a greater role in decision-making at the next level.
Keywords: digital farming; Agriculture 4.0; data-driven decision making; precision farming